The consensus immunoscore: toward a new classification of colorectal cancer - Lanzi, Anastasia (Oncoimmunology, 2020)
In its latest edition, the WHO classification of the Digestive System Tumors introduced for the first time the immune response as essential and desirable diagnostic criteria for colorectal cancer. The immune response within the tumor microenvironment is therefore clinically relevant. The consensus Immunoscore has a prognostic value that has been confirmed in a meta-analysis on more than 10,000 patients, and it provides a reliable estimate of the recurrence risk in colon cancer. The international validation of the prognostic value of the consensus Immunoscore for time to recurrence, disease-free survival and overall survival in colon cancer together with its predictive value of response to chemotherapy provides valuable information for patient care management.